High‐Resolution Soil Moisture Data Reveal Complex Multi‐Scale Spatial Variability Across the United States - Noemi Vergopolan; Justin Sheffield; Nathaniel W. Chaney; Ming Pan; Hylke E. Beck; Craig R. Ferguson; Laura Torres‐Rojas; Felix Eigenbrod; Wade Crow; Eric F. Wood (Geophysical Research Letters)
Abstract Soil moisture (SM) spatiotemporal variability critically influences water resources, agriculture, and climate. However, besides site‐specific studies, little is known about how SM varies locally (1–100‐m scale). Consequently, quantifying the SM variability and its impact on the Earth system remains a long‐standing challenge in hydrology. We reveal the striking variability of local‐scale SM across the United States using SMAP‐HydroBlocks — a novel satellite‐based surface SM data set at 30‐m resolution. Results show how the complex interplay of SM with landscape characteristics and hydroclimate is primarily driven by local variations in soil properties. This local‐scale complexity yields a remarkable and unique multi‐scale behavior at each location. However, very little of this complexity persists across spatial scales. Experiments reveal that on average 48% and up to 80% of the SM spatial information is lost at the 1‐km resolution, with complete loss expected at the scale of current state‐of‐the‐art SM monitoring and modeling systems (1–25 km resolution).